2023
DOI: 10.1111/nph.18684
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term variation in leaf‐level water use efficiency in a tropical forest

Abstract: Summary The representation of stomatal regulation of transpiration and CO2 assimilation is key to forecasting terrestrial ecosystem responses to global change. Given its importance in determining the relationship between forest productivity and climate, accurate and mechanistic model representation of the relationship between stomatal conductance (gs) and assimilation is crucial. We assess possible physiological and mechanistic controls on the estimation of the g1 (stomatal slope, inversely proportional to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…Measurement of the stomatal slope parameter is fraught with trade‐offs and compromises and a number of approaches have been used to estimate this important physiological parameter (Ball et al, 1987; Bernacchi et al, 2006; Davidson et al, 2023; Medlyn et al, 2011; Miner et al, 2017; Wu et al, 2020). Here, using an in situ steady‐state‐survey approach—enabled by canopy access and typically low wind speeds at the field site—we showed that the time since inserting a leaf into the leaf chamber impacted A and g sw and that the leaf‐WUE was higher (lower m ) when measured at steady‐state compared with measurements made within 90 s of inserting the leaf (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Measurement of the stomatal slope parameter is fraught with trade‐offs and compromises and a number of approaches have been used to estimate this important physiological parameter (Ball et al, 1987; Bernacchi et al, 2006; Davidson et al, 2023; Medlyn et al, 2011; Miner et al, 2017; Wu et al, 2020). Here, using an in situ steady‐state‐survey approach—enabled by canopy access and typically low wind speeds at the field site—we showed that the time since inserting a leaf into the leaf chamber impacted A and g sw and that the leaf‐WUE was higher (lower m ) when measured at steady‐state compared with measurements made within 90 s of inserting the leaf (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Here, using an in situ steady‐state‐survey approach—enabled by canopy access and typically low wind speeds at the field site—we showed that the time since inserting a leaf into the leaf chamber impacted A and g sw and that the leaf‐WUE was higher (lower m ) when measured at steady‐state compared with measurements made within 90 s of inserting the leaf (Figure 2). Most of the survey‐type gas exchange measurements are made after a short acclimation time, typically less than 90 s (Bernacchi et al, 2006; Davidson et al, 2023; Leakey et al, 2006; Lin et al, 2015; Wu et al, 2020). However, it is known that stomata react more slowly to changes at the leaf surface than photosynthesis (Lawson & Vialet‐Chabrand, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations